The trend of relevance of value of accounting information: a study on pharmaceutical companies listed in the Tehran Stock Exchange - Norallah Khodadadi; Mehrdad Ghanbry; Babak Jamshidinavid; Javad Masudi (Shahid Beheshti University of Medical Sciences, 2023)
Background: Financial statements are one of the main ways for companies to communicate in order to provide financial and non-financial information to their stakeholders. The purpose of this research was to investigate the relevance of accounting information value. It was for pharmaceutical companies active in Tehran Stock Exchange. Methods: This descriptive-correlational study was conducted on 26 pharmaceutical companies admitted to the stock exchange during the period of 2000 to 2019. The method of collecting information was based on two library models and the information included in the financial statements of the companies. To estimate the value relevance of accounting information in this study, the non-parametric method of classification and regression tree (CART) was used, which automatically includes non-linear relationships and interactions between variables, and simple linear regression was used to test the trend of value relevance. Results: The results showed that the trend of relevance of the composite value of accounting information increased during the research period for pharmaceutical companies, but it was not statistically significant. The results of the relevance of the value of single variables show a decrease in the relevance of the value of known intangible assets, which includes goodwill and software, and an increase in the relevance of the value of alternative performance measures for pharmaceutical companies. Conclusion: The relevance of the accounting information value of pharmaceutical companies allows investors to easily adjust their investment strategies in the Bahadra Stock Exchange and make informed decisions to achieve their goals and allocate resources to more profitable investments.